Changes in Amino Acid Profiles and Bioactive Compounds of Thai Silk Cocoons as Affected by Water Extraction - Chuleeporn Bungthong; Sirithon Siriamornpun (Molecules, 2021)
Silk proteins have many advantageous components including proteins and pigments. The proteins—sericin and fibroin—have been widely studied for medical applications due to their good physiochemical properties and biological activities. Various strains of cocoon display different compositions such as amino-acid profiles and levels of antioxidant activity. Therefore, the objectives of this study were to find a suitable silk protein extraction method to obtain products with chemical and biological properties suitable as functional foods in two strains of Bombyx mori silk cocoon (Nangsew strains; yellow cocoon) and Samia ricini silk cocoon (Eri strains; white cocoon) extracted by water at 100 °C for 2, 4, 6 and 8 h. The results showed that Nangsew strains extracted for 6 h contained the highest amounts of protein, amino acids, total phenolics (TPC) and total flavonoids (TFC), plus DPPH radical-scavenging activity, ABTS radical scavenging capacity, and ferric reducing antioxidant power (FRAP), anti-glycation, α-amylase and α-glucosidase inhibition. The longer extraction time produced higher concentrations of amino acids, contributing to sweet and umami tastes in both silk strains. It seemed that the bitterness decreased as the extraction time increased, resulting in improvements in the sweetness and umami of silk-protein extracts.